NiRu nanoparticles encapsulated in a nitrogen-doped carbon matrix as a highly efficient electrocatalyst for the hydrogen evolution reaction. Issue 39 (25th September 2020) - Xu, Shikai; Li, Zhiqiang; Chu, Kainian; Yao, Ge; Xu, Yang; Niu, Ping; Zheng, Fangcai
Abstract : We synthesize ultrafine NiRu nanoparticles embedded in a nitrogen-doped carbon matrix through direct carbonization of Ru-doped Ni-based MOFs. As expected, NiRu2 @NC-600 exhibits superior electrocatalytic activity for the HER in acidic and alkaline electrolytes. Abstract : The design and fabrication of low-cost, efficient, and robust electrocatalysts for the hydrogen evolution reaction (HER) is of great importance in accelerating the development of water electrolysis technology. Herein, NiRu alloy nanostructures embedded in a nitrogen-doped carbon matrix (NiRu@NC) have been fabricated through a facile metal–organic framework-derived (MOF-derived) strategy. Benefiting from their advantages in the unique structures and components, the resulting NiRu@NC possesses excellent activity and durability towards the HER, which exhibits low overpotentials of 85 and 53 mV at a current density of 10 mA cm −2 in acidic and alkaline electrolytes, respectively. Furthermore, NiRu2 @NC-600 also exhibits excellent hydrogen oxidation reaction (HOR) activity in an alkaline electrolyte. Therefore, this work provides a facile MOF-derived strategy for the design and synthesis of low-cost and efficient electrocatalysts for the HER.